EDUKASI PENCEGAHAN BULLYING MELALUI PENYULUHAN INTERAKTIF BAGI SISWA SMP NEGERI 2 PANTAI CERMIN OLEH MAHASISWA KKN KELOMPOK 6 DESA NAGA KISAR - Muliatik, Sri; Rahmatullah, Muhammad Khaidir; Fatta, Muhammad Ihsanul; Lestari, Tria Ayu (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2025)
emotional, and academic development. This phenomenon remains prevalent at the junior high school level, requiring systematic preventive interventions. The Community Service Program (Kuliah Kerja Nyata or KKN) serves as a strategic initiative in supporting schools to create safe and child-friendly learning environments. This study aims to describe the effectiveness of interactive counseling conducted by KKN Group 6 students of Naga Kisar Village in raising students’ awareness and understanding of bullying prevention at SMP Negeri 2 Pantai Cermin. This research employed a descriptive qualitative approach with an action research design. The subjects consisted of 45 seventh- and eighth-grade students selected through purposive sampling. Data were collected using participatory observation, pre- and post-counseling questionnaires, interviews, and documentation, then analyzed using. The findings revealed a significant improvement in students’ understanding of the definition of bullying (from 38% to 82%), types of bullying (from 41% to 85%), and willingness to report bullying cases (from 47% to 79%). Interactive counseling using educational videos, group discussions, role-playing, and reflective quizzes proved effective in increasing student participation and encouraging moral courage to reject bullying. In conclusion, interactive counseling is an effective strategy for early bullying prevention. KKN students play a vital role as community change agents by bridging academic theory with practical implementation in schools. For sustainability, follow-up programs such as child-friendly school initiatives and ongoing collaboration with teachers, counselors, and parents are strongly recommended.